The Philippines under Spain, Book V (1590-1593) : Reproduction of the original Spanish documents with English translation - Licuanan, Virginia Benitez; Mira Jose Llavador; Mira Jose Llavador (Manila : National Trust for Historic and Cultural Preservation of the Philippines, 1994)
Church vs State Bishop Domingo Salazar and Governor Gomez Perez Dasmariñas
Keywords: Philippines -- History -- 1564-1898.